Are learning styles useful? A new software to analyze correlations with grades and a case study in engineering - Molina-Cabello, Miguel Ángel; Thurnhofer-Hemsi, Karl; Molina Cabello, David; Palomo-Ferrer, Esteban José (Wiley, 2023)
Knowing student learning styles represents an effective way to design the most suitable methodology for our students so that performance can improve with less effort for both students and teachers. However, a methodology is usually set in teaching guides according to the previous academic year's information without any knowledge of our current audience. In this work, a new software for learning styles and grade analysis based on the Honey‐Alonso Learning Styles Questionnaire has been proposed. This tool proposes the average learning style profiles of a given course by clustering student learning styles and analyzes the possible relation between grades and learning style profiles. By using that program, three different courses from Computer Sciences Engineering degrees during an academic year have been analyzed. The obtained results in our specific context exhibit that possible relation. This information could be useful to understand how students approach learning materials.
Keywords: Enseñanza asistida por ordenador; Tecnología educativa; Academic performance; Evaluation; Grade; Learning style; Virtual campus